OP07 Assessing models of ACP in primary care, the meta-LARC trial: part 1 design and realization of a us-canada study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Totten, A; Michaels, L; Fagnan, L; Dorr, D; Legare, F
Abstract : Background and aims: Advance care planning (ACP) has the potential to reduce suffering and improve outcomes in serious illness, but its implementation has been limited. A consortium of seven Practice Based Research Networks (PBRNs) in the US and Canada known as Meta-LARC designed a cluster randomized comparative effectiveness trial of two models of ACP in primary care practices. Methods: Meta-LARC facilitated identification of primary care concerns and topics through collaboration among researchers, PBRN directors, clinicians and patient/family advisors. Over 2 months, we used the PBRNs to quickly assess interest, develop options, assess feasibility, refine ideas and obtain buy-in. Through this iterative process, we identified an existing ACP program to study (the Serious Illness Care Program by Ariadne Labs) and developed a proposal, research protocol and a stakeholder engagement plan. Results: The trial, agreed to by all seven PBRNs, was funded by the Patient Centered Outcomes Research Institute and began in November 2017. This panel will discuss the key decision steps and drivers for the trial design (Part 1) and the accomplishments to date including engaging stakeholders (Part 2), adapting ACP training for teams (Part 3), obtaining ethics approval in two countries (Part 4), supporting ACP implementation in diverse primary care practices (Part 5) and developing patient-reported measures of goal concordant care (Part 6). Conclusion: PBRN networks provide an important infrastructure that can facilitate design of a large, complex study of ACP with the potential to influence the spread of ACP in primary care practices in at least two countries.